2018
DOI: 10.1021/acsami.8b08503
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivated Polymeric Bilayer Actuators Fabricated via 3D Printing

Abstract: 4D printing is an emerging additive manufacturing technology that combines the precision of 3D printing with the versatility of smart materials. 4D printed objects can change their shape over time with the application of a stimulus (i.e., heat, light, moisture). Light driven smart materials are attractive because light is wireless, remote, and can induce a rapid shape change. Herein, we present a method for fabricating polymeric bilayer actuators via 3D printing which reversibly change their shape upon exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…[ 209 ] 3D printing of shape changing polymers, also termed 4D printing, [ 16,210–217 ] is an emerging technology with a great capacity for fabricating complex 3D structures, providing great potential for a wide range of applications. Various shape changing polymers including hydrogels, [ 98,99,111,117,118,188–201,203–220 ] shape memory polymers, [ 153,221–227 ] liquid crystal elastomers, [ 228–233 ] and silicone‐based elastomers [ 234–237 ] have been demonstrated to undergo 4D printing.…”
Section: Retaining Materials Properties Of Printed Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 209 ] 3D printing of shape changing polymers, also termed 4D printing, [ 16,210–217 ] is an emerging technology with a great capacity for fabricating complex 3D structures, providing great potential for a wide range of applications. Various shape changing polymers including hydrogels, [ 98,99,111,117,118,188–201,203–220 ] shape memory polymers, [ 153,221–227 ] liquid crystal elastomers, [ 228–233 ] and silicone‐based elastomers [ 234–237 ] have been demonstrated to undergo 4D printing.…”
Section: Retaining Materials Properties Of Printed Polymersmentioning
confidence: 99%
“…reported, a photoresponsive azobenzene‐containing LCE could be printed on the surface of a Kapton film. [ 229 ] Due to the fully reversible trans–cis photoisomerization of azobenzene upon irradiation of light with different wavelength, [ 246 ] the bilayer structures exhibits rapid actuation with full cycles completed within seconds. It was found that a lengthy alkyl spacer between the AB mesogen affects the photo‐induced bending angle and photo generated stresses.…”
Section: Retaining Materials Properties Of Printed Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The Tisue Scribe has been used for various applications in tissue engineering, dental, and materials testing/optimization research, such as is used in biofabricating 3D tumor models, 79 cell-laden hydrogels for cell-cell interaction study, 80 nanocomposite hydrogels for cell migration study, 81 gelatin hydrogel properties and 3D bioprinting process optimization, 82 highly elastomeric and property-tailorable hydrogels, 83 3D printed smart dental implants, 84 biomaterials and 3D/4D printed thermosensitive and photoactivated smart materials, 85,86 and 3D printed porous structures with shape memory properties. 87,88 Advanced Solutions Inc.'s BIOBOT BASIC.…”
Section: Low-cost Microextrusion-based Bioprintersmentioning
confidence: 99%
“…The flow‐induced alignment of the LC oligomers was also applied to the preparation of LC elastomers through 3D printing technology . A mixture containing LC oligomers was used as ink for 3D printing, which was extruded under melting.…”
Section: Recent Developmentmentioning
confidence: 99%